2002
DOI: 10.1097/00000539-200205000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Systolic Hypertension Is Associated with Adverse Outcomes from Coronary Artery Bypass Grafting Surgery

Abstract: Isolated systolic hypertension is associated with a 40% increase in the likelihood of perioperative cardiovascular morbidity in coronary artery surgery patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(83 citation statements)
references
References 39 publications
2
75
1
5
Order By: Relevance
“…40 PP, necessarily increased in patients with isolated systolic hypertension, can be singled out as a greater predictor of risk for stroke, heart failure, coronary artery disease, and renal failure than diastolic blood pressure. 3,46,47 This study showed a significant and progressive increase in the risk of renal composite above a PP threshold of 40 mm Hg. The adjusted OR is 1.49 with a 95% CI of 1.17 to 1.89 for patients with a preoperative PP of 40 to 60 mm Hg versus patients with PP Յ40 mm Hg; the adjusted OR is 4.87 with a 95% CI of 1.86 to 12.75 for patients with preoperative PP Ͼ100 mm Hg versus those with PP Յ40 mm Hg.…”
Section: Pp Hypertensionmentioning
confidence: 50%
See 2 more Smart Citations
“…40 PP, necessarily increased in patients with isolated systolic hypertension, can be singled out as a greater predictor of risk for stroke, heart failure, coronary artery disease, and renal failure than diastolic blood pressure. 3,46,47 This study showed a significant and progressive increase in the risk of renal composite above a PP threshold of 40 mm Hg. The adjusted OR is 1.49 with a 95% CI of 1.17 to 1.89 for patients with a preoperative PP of 40 to 60 mm Hg versus patients with PP Յ40 mm Hg; the adjusted OR is 4.87 with a 95% CI of 1.86 to 12.75 for patients with preoperative PP Ͼ100 mm Hg versus those with PP Յ40 mm Hg.…”
Section: Pp Hypertensionmentioning
confidence: 50%
“…[1][2][3][4][5][6]8,10,11,14,16 Critical to prevention and therapy is identification of risk factors. Previous risk profiles were limited to single-center experi- ences with site-specific data fields and hence restricted generalization, small sample size without a validation cohort, and incomplete characterizations of patients.…”
Section: Discussion General Overview: Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Ізольована систолічна гіпертензія в осіб з опера-тивними втручаннями на коронарних судинах під-вищує періопераційну серцево-судинну смертність на 40 % [5]. Загалом в осіб, старших від 65 років, ізольована систолічна гіпертензія в періоперацій-ний період пов'язана з підвищеним ризиком смерті [19].…”
Section: рекомендаціїunclassified
“…[15][16][17] A recent study of patients undergoing coronary artery bypass grafting (CABG) found that ISH was an independent cardiac risk factor and was associated with a 40% increase in the likelihood of perioperative cardiovascular morbidity. 18 Clinically important differences in comorbidities and surgical considerations between cardiac and non-cardiac surgery suggests the need for a similar study in non-cardiac surgery to investigate the incidence of perioperative myocardial ischemia in ISH.…”
Section: Résumémentioning
confidence: 99%